“The impact of the Little Orange Book on how parents/carers manage symptoms of illness in children: A mixed methods study” - Amy Johnson; Kathryn Carruthers; Matthew Breckons; Lynette Harland Shotton (PLoS ONE, 2025)
Background Previous literature has highlighted the complexity of supporting an acutely unwell child and the unnecessary use of services by parents/carers. The Little Orange Book (LOB) was developed as an information resource for parents/carers of young children to assist in managing symptoms of childhood illness and to encourage the appropriate use of healthcare services. Objectives This study aimed to understand parent/carer views and experiences using the Little Orange Book. Specifically, this study focused on barriers and facilitators to use, the impact on parents’ behaviour and the views on improving the LOB. Methods An explanatory sequential mixed-methods approach, including qualitative and quantitative components, was used to collect data regarding parent’s experiences using the LOB. Parents and carers in the North-East of England were invited to participate in an online survey and a subset of these respondents took part in qualitative interviews. One-hundred-and-twenty-eight parents completed the online survey and 16 took part in interviews. Qualitative data were analysed using thematic analysis and quantitative data analysed using descriptive statistical analytical methods. Results Three themes were identified within the data: Increasing parental empowerment in managing their child’s health , Equality of Access to Health-based Literature and Barriers and Facilitators to using the Little Orange Book . Conclusions The Little Orange Book was seen as a valuable form of information to support parents and carers in healthcare decisions. Further development should ensure inclusivity, widen access and view provision of the information as an opportunity for healthcare professionals to engage with parents.